Kangshujiangu granules improve NAFLD via cross-organ autophagy activation shared with osteoporosis - Wang, Ningxi; Song, Li; Peng, Yue; Wei, Langqiu; Long, Zhaofan; Wang, Che; Liu, Qiling; Shi, Chuandao (Frontiers in Pharmacology, 2025)
BackgroundOsteoporosis (OP), an age-related skeletal disorder characterized by reduced bone mass and deteriorated microarchitecture, and non-alcoholic fatty liver disease (NAFLD), a metabolic condition primarily driven by obesity and insulin resistance (with age as a modifying factor), were investigated in this study. We aimed to elucidate the correlation between OP and NAFLD-associated lipid metabolism, and determine the therapeutic effects and molecular mechanisms of Kangshujiangu granules (KSJG) on NAFLD pathogenesis.MethodsClinical study: 261 patients were stratified by OP T-scores into OP and non-OP groups. Bone density, lipid profiles, and liver function were analyzed for NAFLD-OP correlations. In vivo: 60 female SD rats were randomized into control, NAFLD-OP model, low/medium/high-dose KSJG, and Icariin (ICA) groups. Metabolic indicators and autophagy related proteins were evaluated. In vitro: FFA-induced hepatocytes were treated with Compound C, KSJG, or FF. Cells were divided into six groups: BSA control, FFA model, FFA + Compound C, FFA + KSJG, FFA + FF, and FFA + KSJG + Compound C. Lipid accumulation, metabolic markers, and autophagy proteins were analyzed.ResultsClinical findings: Osteoporosis prevalence exhibited age-dependent elevation. Age, BMI, TC, and TG as independent risk factors for OP (P < 0.05). In vivo results: KSJG granules significantly attenuated body weight, reduce liver wet weight and liver index; improve lipid accumulation and lipid metabolism disorders; increase autophagy levels in liver tissue, reduce the expression of p-Akt, p-mTOR and p-ULK1 (Ser757), and increase the expression of p-AMPK and p-ULK1 (Ser555) (P < 0.05). In vitro experiments:Both KSJG and FF significantly reduced FFA-induced TG, ALT, AST, and lipid droplet accumulation (P < 0.05). They upregulated LC3Ⅱ/LC3Ⅰ, Atg7, and Beclin 1 while downregulating p62. Additionally, KSJG and FF decreased p-mTOR and p-ULK1 (Ser757) but increased p-AMPK and p-ULK1 (Ser555),while Compound C could reverses this.ConclusionOP exhibited a negative correlation with lipid metabolism indexes of NAFLD. Bilateral ovariectomy (OVX) simultaneously induced OP and NAFLD, while KSJG granules ameliorated lipid dysregulation via autophagy modulation. KSJG granules enhanced autophagy activation through the AMPK/ULK1 (Ser555) pathway, thereby alleviating NAFLD-associated lipid metabolic disturbances.